DNA methylation markers for cancer risk prediction of vulvar intraepithelial neoplasia - Thuijs, Nikki B. (Int J Cancer, 2021)
Current clinical and histological classifications are unable to determine the risk of vulvar squamous cell carcinoma (VSCC) in high‐grade vulvar intraepithelial neoplasia (VIN), making prognostic biomarkers highly needed. We studied host‐cell DNA methylation markers in high‐grade squamous intraepithelial lesion (HSIL) and differentiated VIN (dVIN) without VSCC, in HSIL and dVIN adjacent to VSCC and in human papillomavirus (HPV) positive and negative VSCC, relative to control vulvar tissues. A series of 192 formalin‐fixed paraffin‐embedded vulvar samples, including VSCC (n = 58), VIN adjacent to VSCC (n = 30), VIN without VSCC during follow‐up (n = 41) and normal vulvar tissues (n = 63), were tested for 12 DNA methylation markers with quantitative multiplex methylation‐specific PCR (qMSP). HPV status was determined by p16(INK4A) immunohistochemistry and high‐risk HPV PCR analysis. Logistic regression analyses were used to determine methylation patterns and methylation marker performance for VIN and VSCC detection. Methylation markers showed significantly higher methylation levels with increasing severity of disease. VIN adjacent to VSCC showed a similar methylation‐high pattern as VSCC, while VIN without VSCC displayed a heterogeneous methylation pattern. Vulvar carcinogenesis is associated with increased DNA methylation. Higher DNA methylation levels in VIN seem to reflect higher cancer risk, emphasizing the high potential of DNA methylation biomarkers in the diagnostic workup of VIN. As a next step, longitudinal studies are needed to verify the prognostic value of methylation biomarkers as a clinical tool for stratification of cancer risk in women with VIN.